An analysis of pump thrombus events in patients in the HeartWare ADVANCE bridge to transplant and continued access protocol trial - Najjar, Samer S; Slaughter, Mark S; Pagani, Francis D; Starling, Randall C; McGee, Edwin C; Eckman, Peter; Tatooles, Antone J; Moazami, Nader; Kormos, Robert L; Hathaway, David R; Najarian, Kevin B; Bhat, Geetha; et al. (The Journal of heart and lung transplantation, 2014)
The HeartWare left ventricular assist device (HVAD, HeartWare Inc, Framingham, MA) is the first implantable centrifugal continuous-flow pump approved for use as a bridge to transplantation. An infrequent but serious adverse event of LVAD support is thrombus ingestion or formation in the pump. In this study, we analyze the incidence of pump thrombus, evaluate the comparative effectiveness of various treatment strategies, and examine factors pre-disposing to the development of pump thrombus. The analysis included 382 patients who underwent implantation of the HVAD as part of the HeartWare Bridge to Transplant (BTT) and subsequent Continued Access Protocol (CAP) trial. Descriptive statistics and group comparisons were generated to analyze baseline characteristics, incidence of pump thrombus, and treatment outcomes. A multivariate analysis was performed to assess significant risk factors for developing pump thrombus. There were 34 pump thrombus events observed in 31 patients (8.1% of the cohort) for a rate of 0.08 events per patient-year. The incidence of pump thrombus did not differ between BTT and CAP. Medical management of pump thrombus was attempted in 30 cases, and was successful in 15 (50%). A total of 16 patients underwent pump exchange, and 2 underwent urgent transplantation. Five patients with a pump thrombus died after medical therapy failed, 4 of whom also underwent a pump exchange. Survival at 1 year in patients with and without a pump thrombus was 69.4% and 85.5%, respectively (p = 0.21). A multivariable analysis revealed that significant risk factors for pump thrombus included a mean arterial pressure > 90 mm Hg, aspirin dose ≤ 81 mg, international normalized ratio ≤ 2, and Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) profile level of ≥ 3 at implant. Pump thrombus is a clinically important adverse event in patients receiving an HVAD, occurring at a rate of 0.08 events per patient-year. Significant risk factors for pump thrombosis include elevated blood pressure and sub-optimal anti-coagulation and anti-platelet therapies. This suggests that pump thrombus event rates could be reduced through careful adherence to patient management guidelines.